Sukuk Negara as Financing Strategy for Renewable Energy Infrastructure: Case Study of Muara Laboh Geothermal Power Project - Handayani, Dian; Surachman, Eko Nur (International Journal of Energy Economics and Policy, 2017)
The importance of renewable energy development is so imminent. It will benefit the society not only by fulfilling the electricity shortage but also by reducing the amount of pollution. However, the funding of the project is still challenging for the Government. One financing alternative is Sovereign Sukuk (Sukuk Negara). This study investigates the possibilities of Sukuk Negara to finance renewable energy project with the case study of Muara Laboh Geothermal Power Plant. The analysis uses two perspectives including legal aspect and financial aspect. Study literature and interview are used in the legal analysis by exploring specific regulations regarding the Sukuk Negara and interviewing Sukuk administrator and issuer. Secondly, financial analysis using discounted cash flow (DCF), net present value (NPV) and internal rate of return (IRR). The result is Sukuk Negara is feasible as the source of financing Muara Laboh Geothermal Power Project. Keywords: Renewable Energy; Sovereign Sukuk; Infrastructure financing. JEL Classifications: E62, R42, H74, H76, G12